Improving The First Semester Students Vocabulary Mastery By Using Ventriloquism Technique - Adipramono, Raditya (Journal of English and Education (JEE), 2013)
The objectives of this research are to find out whether teaching vocabulary by usingventriloquism as a teaching aid is effective, how this technique can improve students’ vocabulary, and whether there is any significant difference between students taught before the treatment and after the treatment. This research is an action research. The respondents of the research were selected randomly. The respondents are 45 students of the first semester of English Department Faculty of Letters Ahmad Dahlan University in Academic Year 2011/2012. The research instrument used by the researcher was the test and questionnaire. The data in the research are mainly gathered through the use of pre-test and post-test. After the data were collected, the researcher analyzed them. The researcher used questionnaire to see the students’ response to this method when it was applied in teaching and learning process. The questionnaire was used to support the primary data from the teaching learning activities and the test. The finding of the research shows that there is a significant difference between teaching vocabulary before using ventriloquism and after using ventriloquism. Before the treatment, the mean is 59.35, the standard deviation is 6.47. After the treatment, the mean is 74.77, while the standard deviation is 15.99. It means that there is a significant difference in teaching vocabulary before using ventriloquism and after using ventriloquism.